2020
DOI: 10.1186/s13018-020-01786-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on the outcome of patients with aseptic femoral head necrosis treated with percutaneous multiple small-diameter drilling core decompression: a retrospective cohort study based on magnetic resonance imaging and equivalent sphere model analysis

Abstract: Background: Aseptic necrosis of the femoral head (ANFH) has a high incidence in the community and causes substantial problems with health as well as economic and social stress. Core decompression is the most commonly used treatment for early ANFH. Although many studies have reported on the efficacy of femoral head core decompression surgery for ANFH, there are still some shortcomings in assessing the severity of femoral head necrosis, the location distribution, and changes in necrotic lesions before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…It has also been noted that if patients with ANFH are not treated promptly and effectively as required, FHC will occur in approximately 70% of patients within 1 to 4 years as the disease progresses. 26,27 The results of this study showed that hormoneinduced femoral osteonecrosis accounted for a high proportion in the etiology of postoperative FHC in patients with Ficat I, II, and III stages of ANFH, and the range of necrosis was large. High-energy damage was the common damage mechanism, and the preoperative waiting time was long.…”
Section: Discussionmentioning
confidence: 71%
“…It has also been noted that if patients with ANFH are not treated promptly and effectively as required, FHC will occur in approximately 70% of patients within 1 to 4 years as the disease progresses. 26,27 The results of this study showed that hormoneinduced femoral osteonecrosis accounted for a high proportion in the etiology of postoperative FHC in patients with Ficat I, II, and III stages of ANFH, and the range of necrosis was large. High-energy damage was the common damage mechanism, and the preoperative waiting time was long.…”
Section: Discussionmentioning
confidence: 71%
“…The ideal state should be treated before the collapse of the femoral head, and early treatment must require an early diagnosis, otherwise SONFH patients would lose the optimal treatment opportunity, resulting in a poor prognosis. Current magnetic resonance imaging (MRI) was the gold standard of early SONFH, and compared to X-ray ray and CT scan technology, MRI could be diagnosed several weeks after patient onset [ 32 ]. However, with the understanding of other diseases of the hip joint, such as transient osteoporosis of hip, or bone marrow edema syndrome (BMES), bone cyst of the femoral head, subchondral incomplete fracture and rapid progressive osteoarthritis, SONFH was frequently confused by the above diseases in MRI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In its progression, FHN leads to the collapse of the femoral head in a large number of patients, with 67% developing collapse even without the manifestation of clinical symptoms [ 12 , 23 ]. Accurate disease staging is thus imperative for FHN to dictate the right course of treatment, particularly in younger patients who may be able to avoid total hip arthroplasty and preserve the native joint [ 24 ].…”
Section: Discussionmentioning
confidence: 99%